Pengaruh Kompetensi dan Human Relationship terhadap Kinerja Guru SMA di Aceh Utara - Sullaida Sullaida; Nurmala Nurmala; Azhar Azhar (Jurnal Visioner & Strategis, 2021)
The purpose of this study was to determine the effect of Competence and Human Relationship on the Performance of High School Teachers in North Aceh District. The data used in this study were 140 high school teachers in North Aceh Regency. The analytical tool used is SPSS . The results showed that competence and human relationships had a significant effect on the performance of high school teachers in North Aceh Regency. Competence has a significant effect on the performance of high school teachers in North Aceh Regency. Human relationship has a significant effect on the performance of high school teachers in North Aceh Regency.Keywords: Competence, Human Relationship, Teacher Performance